Phycotechnology applications and mechanisms - Othman, Rashidi; Shaharuddin, Ruhul Izzati; Mat Ali, Qurratu Aini; Johari, Nursyafica Nadia; Ismail, Muhammad Hanafi (Nova Science Publishers, Inc., 2024)
Cleanliness is not only on application of water to worship but also from safety aspect for daily usage like drinking water and recreation. Regrettably, this tiny volume of water that available on earth is under severe stress because of speedy rise in populace, urbanisation, and untenable utilisation of water in agricultural and industrial setups. Thus, this chapter has aimed to explore various groups of selected algae that can be employed as potential biosorption agent for inorganic contaminants in polluted aquatic ecosystem. The phycoremediation process involves the microalgae application for bioremediation (bioconcentration, biotransformation, biosorption, sequestration, assimilation) of contaminants such as phosphate, nitrate and heavy metals from the discarded waters in an ecological way, without producing secondary harmful compounds. When compared to traditional treatment procedures, it is one of the sound alternative approaches for treating garbage and waste waters feasibly, cost-effectively and sustainably and has the additional advantage of decreasing the carbon footprint. Phycoremediation schemes must aim at examining and developing hyperaccumulator algal species from existing algal variety to deal with the ever-increasing worldwide water pollution. This integrated arrangement is an outstanding example of attaining multiple objectives while realising social, environmental and industrial aspects of sustainable growth policies, preserving natural resources, and at the same time improving the quality of lives of the population rising on the global level.